2017
DOI: 10.1021/acs.chemmater.7b00802
|View full text |Cite
|
Sign up to set email alerts
|

Plant Flavonoid-Mediated Multifunctional Surface Modification Chemistry: Catechin Coating for Enhanced Osteogenesis of Human Stem Cells

Abstract: Application of surface chemistry using bioactive compounds enables simple functionalization of tissue-engineering scaffolds for improved biocompatibility and regenerative efficacy. Recently, surface modifications using natural polyphenols have been reported to serve as efficient multifunctional coating; however, there has yet to be any comprehensive application in tissue engineering. Here, we report a simple, multifunctional surface modification using catechin, a phenolic compound with many biological function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 51 publications
1
49
0
1
Order By: Relevance
“…However, our data is insufficient to conclude that the simple mixture of EGCG and gelatin was ineffective at retaining the polyphenol in the gelatin sponge. Other studies have addressed the efficacy of the non-chemical modification technique using EGCG in combination with other biomaterials, including synthetic polymers 3,22) , alpha-tricalcium phosphate 34) , and collagen 35) for bone tissue engineering. Some studies showed that physical adsorption of EGCG on the other biomaterials without any chemical modification increased the capacity for bone formation 3,21,34) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our data is insufficient to conclude that the simple mixture of EGCG and gelatin was ineffective at retaining the polyphenol in the gelatin sponge. Other studies have addressed the efficacy of the non-chemical modification technique using EGCG in combination with other biomaterials, including synthetic polymers 3,22) , alpha-tricalcium phosphate 34) , and collagen 35) for bone tissue engineering. Some studies showed that physical adsorption of EGCG on the other biomaterials without any chemical modification increased the capacity for bone formation 3,21,34) .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is consensual that EGCG is a strong antioxidant and anti-inflammatory agent 8) . Additionally, the presence of EGCG in biomaterials treated by coating or modification approaches alters the materials properties, including wettability, charge, and calcium deposition 18,22) . After the transplantation of sponges, the rapid release of EGCG from NC-vhEGCG-GSs might have caused the loss of the pharmacological effect of EGCG and changed the surface properties of the sponges over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such bioinspired approaches have recently shown promising pro-osteogenic potential for tissue engineering and regenerative medicine applications [4,8]. For example, a catechin-hydrate-coated substrate markedly enhanced the osteogenic differentiation and mineralization of hASCs [9]. In addition, catechin-coated polycaprolactone nanofiber scaffolds implanted in a critical-sized calvarial defect prompted a significant improvement in bone formation and density, as well as collagen deposition [9].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Die resultierenden Beschichtungen zeigten nicht nur antibakterielle und antioxidative Eigenschaften, sondern konnten auch zur Modulation der optischen Eigenschaften von anorganischen Nanopartikeln wie Gold‐Nanostäbchen verwendet werden (Abbildung d). Viele Beispiele sind gefolgt und ermöglichen eine große Familie von pflanzlichen Phenolverbindungen, die zur Oberflächenmodifikation durch oxidative Selbstpolymerisation verwendet werden können . Statt des basischen pH‐Bereichs kann auch UV‐Strahlung die oxidative Selbstpolymerisation von Phenolverbindungen induzieren; dieser Ansatz wurde zum Aufbau strukturierter dünner Schichten verwendet (Abbildung e–g) .…”
Section: Dünne Filmeunclassified